Problems Of Learning Local Content In The Bugis Language Learning Process In Sidrap District - Nadir La Djamudi; Rudy Yusuf; Sam hermansyah; Firman Saleh; Ibrahim Ibrahim (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This research aims toknowing the learning problems that occur in the process of teaching and learning Bugis language in learning Bugis language local content in Maritengngae District, Sidrap Regency. This type of research uses a qualitative descriptive approach in the form of a case study with data collection methods, observation, interviews, and distributing questionnaires. The results of the study show that there are 4 learning problems in the teaching and learning process, namely teacher problems, learning device problems, curriculum problems, and student problems. Teacher problems, namely teachers who teach not in accordance with their educational background, curriculum problems, namely the absence of regional language curricula, learning device problems, namely there are no adequate learning tools